Mountain Cryosphere Landscapes in South America: Value and Protection - Ruiz Pereira, Sebastián; Alvarado Peterson, Voltaire; Trombotto, Dario Tomas (Conservation)
Mountain landscapes support hydric and biodiversity potential under different owner‐ ship and land use perspectives. A focal point justifying their preservation is often the legislation’s ethical endorsement. Yet, when scales for assessment diverge without a common analytical purpose, the protective measures may become either ambiguous or insufficient. By considering that moun‐ tain cryosphere landscapes have both subjective and supply values, we focused on approaches to protect them and examined conceptual dissonances in their assessment. This ambiguity was exam‐ ined by analyzing the hydric storage potential of the mountain cryosphere in semi‐arid regions in the Andes. We reviewed the technical aspects of cryosphere hydrology and how current legislation aims to preserve freshwater supply and non‐instrumental value. The analysis found a clash between instrumental and non‐instrumental values and, most importantly, the neglect of a temporal dimen‐ sion for landscape evolution. Particularly, landscape protection becomes suboptimal as scales of analysis for use and non‐use values diverge. Therefore, we recommend analyzing mountain cry‐ osphere landscapes as overlapped sub‐units bearing a unified potential (future value) as a hydric resource. This analysis should fit the most inclusive scale on which transaction costs reflecting needs and insurance values reflecting management quality are optimal. Fil: Ruiz Pereira, Sebastián. Pontificia Universidad Catolica de Chile. Escuela de Ingeniería; Chile Fil: Alvarado Peterson, Voltaire. Universidad de Concepción; Chile Fil: Trombotto, Dario Tomas. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina